PERISTILAHAN DALAM UPACARA ADAT PAYONG LILEN MASYARAKAT MELAYU DI DESA SEMUDUN KABUPATEN MEMPAWAH - Suwito, Jery Arifin; Heryana, Nanang; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe ritual of the Payong liIen which is carried out by Malay people in Semudun, Mempawah, is a form of cultural traditions. Implementation of the traditional ceremony has certain purposes both in terms of the equipment used and the stages taken.This research examines the ins and outs of the meaning, from the linguistic sides through semantic studies. The object of this research focuses on the components of meaning in the equipment used as well as the procession in the ritual of Payong lilen.The method of this research was a descriptive method with qualitative form. The initial data was taken through surveys and observation over the object of the research.Based on the data analysis, 18 types of equipments were used and 11 processions were carried out in the implementation of the ritual of Payong lilen. Then, it can be concluded that the Ritual Payong lilen has 29 types of terminology which are of equipment and the procession. The obtained terminologies are sireh selike, rokok tembakok, telok ayam kampong, pinang bulat, minyak bau, payong lilen, pakuk, lilen lebah, keminting, duet sen, perapen, pacar,beras kuning, berteh, mengkok puteh, kaen kuning, gamber,kapor sireh, masang lilen, meramu,nyelepangkan kaen kuning, melumor, berabon, bealen, mengamborkan, buang-buang, meminomkan aek, niup lilen, dan moleskin pacar kekening.  Keywords: Terminology of Payong Lilen Traditional Ceremony, Malay community in Semudun village